The Role of Teachers in Forming Citizenship Awareness of Primary School Students - Najwa Ilmi (International Journal of Students Education, 2024)
Education has a very important position for the Indonesian nation in order to shape and build individual character through the process of acquiring knowledge, skills, understanding that is useful in the life of the nation, as well as moral values that will be instilled in individuals. The role of Citizenship Education teachers in raising awareness in students today is very important because of the developments in the times that students have been following since an early age which causes students' awareness to decline. This research uses a qualitative approach method combined with literature research. Researchers searched for data and information through the process of reading articles and journals related to the role of citizenship education teachers in raising awareness of elementary school students in the era of globalization. The literature research process includes selecting relevant literature sources, reading and critical analysis of the selected literature sources, as well as preparing reports on the results of literature studies obtained from various available reference sources so that writing scientific articles can run well. With this qualitative-based research, it is hoped that students will respect teachers more, get used to praying before class starts, students will be more attentive to their friends, dress neatly every day, be more disciplined and obey the rules, and be aware of their obligations as students.